2024
DOI: 10.3390/cancers16061091
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax Resistance in Acute Myeloid Leukemia

Sylvain Garciaz,
Marie-Anne Hospital,
Yves Collette
et al.

Abstract: Venetoclax is a BH3-mimetics agent interacting with the anti-apoptotic protein BCL2, facilitating cytochrome c release from mitochondria, subsequent caspases activation, and cell death. Venetoclax combined with azacitidine (VEN-AZA) has become a new standard treatment for AML patients unfit for intensive chemotherapy. In the phase III VIALE-A study, VEN-AZA showed a 65% overall response rate and 14.7 months overall survival in comparison with 22% and 8 months in the azacitidine monotherapy control arm. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…First-line therapy of eligible older patients continues to be chemotherapy with a combination of anthracycline and cytosine-arabinoside as a backbone; however, the combination of venetoclax and azacitidine or low-dose cytarabine, or low-dose cytarabine with glasdegib, could be the new standard of comparison for persons unfit for intensive therapy. Moreover, in selected studies, the survival of older patients with AML did not exceed 50% in 1 year, and primary resistance to venetoclax was frequent, remaining an unmet clinical need [4][5][6]. To improve venetoclax treatment outcomes, it was shown that a combination of venetoclax with other agents such as S63845, an MCL1 inhibitor, reduced the number of leukemic cells, indicating that MCL1 (S63845) and BCL-2 (venetoclax) inhibitors are synergistic and lead to T-ALL cell apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…First-line therapy of eligible older patients continues to be chemotherapy with a combination of anthracycline and cytosine-arabinoside as a backbone; however, the combination of venetoclax and azacitidine or low-dose cytarabine, or low-dose cytarabine with glasdegib, could be the new standard of comparison for persons unfit for intensive therapy. Moreover, in selected studies, the survival of older patients with AML did not exceed 50% in 1 year, and primary resistance to venetoclax was frequent, remaining an unmet clinical need [4][5][6]. To improve venetoclax treatment outcomes, it was shown that a combination of venetoclax with other agents such as S63845, an MCL1 inhibitor, reduced the number of leukemic cells, indicating that MCL1 (S63845) and BCL-2 (venetoclax) inhibitors are synergistic and lead to T-ALL cell apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%